MICRO AREA TRANSPORTATION OF RESIDUES: A STYLE FORMING THE RED WEATHERING CRUSTS OF CARBONATE ROCKS - Feng Zh.; Wang Sh.; Liu X.; Luo W.; Wang Q. (My University, 2006)
The red weathering crusts of carbonate rocks are usually characteristic of thick-bedded intensely weathered profiles and strongly undulate basement rock surface (i.e., alternative distribution of solution grooves and stone teeth). In this work a typical red weathering crust of carbonate rock, whose parent rock is of homogeneity in composition, is selected in karst terrace, middle Guizhou Province, China. Via field geology, geochemistry, mineralogy, grain size analyses, and in comparison with two neighbouring limestone soils as well, the authors have discussed forming process of the red weathering crusts of carbonate rocks, and demonstrated that micro area transportation of acid-insoluble residues of carbonate rocks is a style of forming the red weathering crusts of carbonate rocks. The weathering front is a main place of geochemical reaction, and at this limited-thick interface, with quick dissolution of carbonates, acid-insoluble residues begin to obviously decompose. On the basis of this, the evolution of weathering crusts is very slow. Weathering intensity of residues at the weathering front is correlative with their weathering history. During the weathering of carbonate rocks, accompanied with gradual downward extension of weathering front, acid-insoluble residues gradually sink downwards. Owing to preferential dissolution of carbonates at solution grooves, the top of weathering crusts at solution grooves is slower and slower than that at stone teeth. Thus, under the action of gravity, residues are gradually transported and piled from stone teeth to solution grooves, and this kind of micro area transportation of residues would stop until gravity equilibrium. As a result, at the scope of a little thin thickness from basement rock surface at solution grooves upwards, weathering residues show in-situ weathering characteristics. More upwards up to the top, different weathering residues are gradually transported and stacked from adjacent stone teeth, and compose principal part of weathering crusts at solution grooves. Their weathering intensity indices show strong undulation with the depth. On the basis of this, weathering crusts start advanced evolution. Through a later long weathering history, the red weathering crusts gradually show weathering features of normal weathering crusts from the top downwards.
Keywords: MICRO AREA TRANSPORTATION; RED WEATHERING CRUST; CARBONATE ROCK; ACID-INSOLUBLE RESIDUE; GUIZHOU